Om så og der som genoptagere for ekstraponerede tid og stedsadverbialer - Christensen, Sune Just (Ny forskning i grammatik, 2017)
The adverbs så and der are both able to represent left dislocated adverbials denoting time. But the Grammatik over det Danske Sprog (GDS) and Ordbog over det Danske Sprog (ODS) both describe how så as opposed to der is not able to represent left dislocated adverbials denoting space. This paper therefore explores in both speech (5,5 hours) and written text (6 million words) the actual distribution of the adverb så and der as representatives for left dislocated adverbials denoting space. The results show that the construction where så represents left dislocated adverbials denoting space is not as infrequent as GDS and ODS prescribes. However alternative analyses of the constructions found in the study may enable a different view at the result.